2002
DOI: 10.1159/000067717
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Cytokine Levels in Serum and Peritoneal Fluid of Women with Endometriosis

Abstract: Endometriosis is a disorder characterised by presence and growth of endometrial tissue outside the uterus, primarily into the peritoneum. The peritoneal fluid (PF) of women with endometriosis undergoes a number of biological changes, including local inflammatory-reparative phenomena and peripheral blood mononuclear cells (PBMC) involvement. These activated cells as well as the endometriotic cells secrete various cytokines with pleiotropic biological activities. Dynamic interplay among cytokines may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
144
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(167 citation statements)
references
References 20 publications
(34 reference statements)
15
144
0
6
Order By: Relevance
“…Increased concentrations of TNF-alpha have already been described in relation to advanced stages 32 , initial stages 33 and in cases where no relation could be perceived with the stage of endometriosis 34 . Concerning deep endometriosis, statistical analysis showed no significant difference in cytokine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of TNF-alpha have already been described in relation to advanced stages 32 , initial stages 33 and in cases where no relation could be perceived with the stage of endometriosis 34 . Concerning deep endometriosis, statistical analysis showed no significant difference in cytokine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Because no reference methods have been published for the measurement of cytokines in serum and blood and because of the large variations in serum concentrations reported in the literature, it is difficult to evaluate the absolute concentrations reported by the present multiplex method (8,16,34,(42)(43)(44)(45)(46)(47)(48). However, to the best of our knowledge the cytokine concentrations measured in sera from healthy people fell within the ranges reported by several other assays, i.e., for IL-1␤, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IL-17, IL-18, IFN-␥, TNF-␣, GM-CSF, and MCP-1 (35, 45, 49 -54 ) (60,61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum MCP-1 level is increased in rats with endometriosis in comparison to those without endometriosis. 20) Several clinical researchers reported that serum MCP-1 is higher in women with endometriosis than in those without [26][27][28] and suggested its usefulness as a biomarker for nonsurgical prediction of endometriosis in humans. 29) Gmyrek et al 27) reported that serum MCP-1 level in women with endometriosis was correlated with severity of the disease.…”
Section: Discussionmentioning
confidence: 99%